Pengelolaan Piutang Sebagai Upaya Meningkatkan Profitabilitas Telkom Indonesia Regional I Sumatera - Mutiara Salsabila; Laylan Syafina (Pusat Riset dan Inovasi Nasional, 2024)
Accounts receivable management is an important process in business activities, especially for large companies such as Telkom Indonesia. Telkom Indonesia as the dominant telecommunications company in Indonesia has a wide customer network, so the management of receivables becomes crucial in maintaining the Company's cash flow and financial health. The application of information technology, such as accounts receivable management systems and data analysis, plays a big role in the management of receivables. The system helps manage customer data, bill tracking, and provides valuable insights into payment trends and customer behavior. Accounts receivable management by Telkom Indonesia involves various strategies ranging from careful credit policies to modern technology and an effective billing approach. These efforts help companies minimize the risk of bad receivables, maintain cash flow, and maintain overall financial stability.